Islamicity Disclosure Index for Shariah Banking: A Case - Nurfalah, Irfan; Rofi'atu, Lu'lu' (Maqasid al-Shariah Review, 2023)
The sharia financial industry is currently a very attractive option with its growth reaching 15% to 20% per year. This fact makes performance evaluation a must for banks. Unfortunately, there are not many indices developed specifically to determine company performance. That is why this paper was prepared with the aim of knowing the performance of the 5 best bank categories from global finance, namely ADIB, BIMB, BMI, IIAB and ABG. The method used in the research is qualitative with descriptive statistics because it involves 2 different indexes namely Islamicity Disclosure Index and Islamicity Performance Index which involves quantitative data. The data used in the study is a data set taken from the financial statements and annual reports of related banks for the period January 1-December 31, 2020. The results of the analysis show that ADIB is the bank that meets the most Islamic reporting indicators followed by BIMB, BMI, ABG and IIAB successively. Meanwhile, the performance index focuses more on distributing benefits not only to shareholders and creditors as in the conventional index but also provides benefits to all parties involved with the bank either directly or indirectly. The results show that these banks still do not meet the criteria for reporting and calculating Islamic performance as a whole.